Magnetotransport of thin film Sr1−xLaxCuO2 on (110) DyScO3. (1st April 2022) - Lustikova, Jana; Wang, Rui-Feng; Zhong, Yong; Wang, ShuZe; Kumatani, Akichika; Ma, Xu-Cun; Xue, Qi-Kun; Chen, Yong P.
Abstract: We report measurements of low-temperature magnetoresistance in Sr1− x La x CuO2 ( x = 0.1) epitaxial thin film grown on (110) DyScO3 single crystal. A positive magnetoresistance which is anisotropic and hysteretic with respect to the in-plane direction of magnetic field appears in Sr1− x La x CuO2 below T = 5 K, coinciding with antiferromagnetic ordering and strong magnetic anisotropy in DyScO3 . The interplay of magnetotransport in epitaxial Sr1− x La x CuO2 with magnetism in the substrate is discussed based on magnetostriction and magnetic relaxation in DyScO3 .